Discovery of jaguar from northeastern China middle Pleistocene reveals an intercontinental dispersal event. (4th March 2023) - Jiangzuo, Qigao; Wang, Yuan; Ge, Junyi; Liu, Sizhao; Song, Yayun; Jin, Changzhu; Jiang, Hao; Liu, Jinyi
ABSTRACT: The fossil record of jaguar lineage (or jaguar-like animal), i.e., Panthera gombaszogensis and Panthera onca, is one of the best and complete among the mammals, making it one of the best-known living species with knowledge of origin, dispersal, and morphological evolution. However, a large gap is present in eastern Asia, which is the gateway for jaguar migration from the Old World to the New World. Here we report a nearly complete mandible from the Middle Pleistocene deposits of Jinyuan Cave, Luotuo Hill of Jinpu New District, Dalian, Liaoning Province of northeastern China. The mandibular morphology fits that of the jaguar, and the dental traits are closest to P. gombaszogensis and Irvingtonian P. onca, but shows robust premolars and represents a new subspecies P. g. jinpuensis . The new find fills the geographic gap for jaguar linage, and supports a northern dispersal routine from western Asia-central Asia-northeastern China to North America, whereas the southern China Early Pleistocene seems to be occupied by a similar sized but taxonomically different pantherine cat.